Study on the effect of clay loading under normal and auto-thermal extrusion to the morphology structure and thermal properties of nylon 6 nanocomposites - Geraldine Chan, Sue Ching (2013)
In this research, the influence of auto-thermal extrusion on the thermal stability and morphology of fabricated polyamide6 (PA6) nanocomposites with varying clay loading and screw speed is discussed. The effect of zero-heat transferred extrusion systems on the thermal degradation rate of organic polymer and inorganic nanoclay is the main focus of this research. A polymer nanocomposite based from polyamide 6 and Cloisite® 20A, commercialized organic modified nanoclay, was prepared by using auto-thermal and conventional melt extrusion system. The morphological characteristics were determined through the application of X-ray diffraction (XRD) and scanning electron microscope (SEM). The thermal stability of compounded PA6/C20A nanocomposite was conducted using thermogravimetric analysis (TGA). The clay content and screw speed of the extruder dictates the quality of the PA6/C20A nanocomposites as well as the auto-thermal or conventional extrusion system itself. The auto-thermal extrusion affects the thermal stability of the melt-processed polymer nanocomposites by allowing even distribution of heat energy throughout the molten compound. However, it has very little effect on the morphology structure of PA6/C20A nanocomposites. As an addition, the screw speed of the extruder also affects the onset degradation temperature of samples produced.